Cavalryman in the Crimea : the Letters of Temple Godman, 5th Dragoon Guards. - Warner, Philip (Pen and Sword Military, 2009)
Among the British troops bound for the Black Sea in May 1854 was a young officer in the 5th Dragoon Guards, Richard Temple Godman, who sent home throughout the entire Crimea campaign many detailed letters to his family at Park Hatch in Surrey. Temple Godman went out at the start of the war, took part in the successful Charge of the Heavy Brigade at Balaklava and in other engagements, and did not return to England until June 1856, after peace had been declared. He took three very individual horses and despite all his adventures brought them back unscathed. Godman's dispatches from the fields of.